Determination of the concentration of gilteritinib in human plasma using HPLC - Yasu, Takeo; Sugi, Tomiyuki; Momo, Kenji; Hagihara, Masao; Yasui, Hiroshi (Biomedical chromatography, 2021)
Gilteritinib, an oral inhibitor of FMS‐like tyrosine kinase 3 (FLT3), is a standard treatment for FLT3‐mutated acute myeloid leukemia. We developed a simple HPLC‐UV‐based method for determining the concentration of gilteritinib in human plasma. The analysis requires the extraction of a 200‐μL plasma sample and the precipitation of proteins by solid‐phase extraction. Gilteritinib was isocratically separated within 10 min using a mobile phase of acetonitrile:0.5% monopotassium phosphate (KH2PO4, pH 3.5, 28:72, v/v) on a Capcell Pack C18 MG II (250 × 4.6 mm) column at a flow rate of 1.0 mL/min and monitored at 250 nm. The calibration curve was found to be linear within a plasma concentration range of 25–2500 ng/mL, with the coefficient of determination (r2) being 0.9997. The coefficients of intra‐day and inter‐day validation were 2.3–3.7 and 1.3–5.2%, respectively. The accuracy and recovery of the assay were −9.6 to 0.1 and >81.8%, respectively. This HPLC‐UV method for determining the plasma concentration of gilteritinib is simple and can be effectively applied to routine drug monitoring.